Thyroid abscess: A report of six cases (Bangladesh Journal of Otorhinolaryngology, 2012)
Thyroid abscess is a rare clinical entity and infrequently encountered. We hereby present a review of six cases-four in the paedriatic and two in the adult age group who presented to our hospital which is a Tertiary care referral centre with thyroid abscess and the management varying from serial aspiration to incision and drainage of abscess. A brief review of literature is also included. DOI: http://dx.doi.org/10.3329/bjo.v18i2.12019 Bangladesh J Otorhinolaryngol 2012; 18(2): 207-211